Impact of food aid on food security in Chipinge Rural District, Zimbabwe - Chikwanda, Florence (Midlands State University, 2018)
The research study focusses on the effects of food aid on food security using the case of Chipinge Rural district, Zimbabwe. The research assesses the negative and positive impact of food aid. Food aid has received much attention worldwide as scholars argue that food aid leads to negative dependency among beneficiaries which is a threat to livelihood activities and leads to underdevelopment while others views food aid as the answer to the problem of food insecurity hence development. Quantitative research method was employed. Ward 1 was randomly selected. Data collection methods included questionnaires and published documents. Questionnaires were administered by 50 household heads, which were calculated using Yamane method of 1967. The research findings showed that food aid has disincentive effects in Chipinge as most of the respondents indicated that as a result of food aid they dropped their livelihood activities and focus their attention on food aid, and a very few wished for food aid to end in the area thus further showing their dependency syndrome. However, on the other hand almost the largest percentage pointed that food aid contributes about 100 percent of the food consumed in their houses hence right targeting by the donor officials. The study recommends that NGOs should address the root cause of food insecurity thus structuring their programs in the way that helps the communities to be sustainably independent rather than dependent